2016
DOI: 10.1186/s12936-016-1239-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of delay in malaria care-seeking behaviour for children 15 years and under in Bata district, Equatorial Guinea

Abstract: BackgroundMalaria remains a major cause of morbidity and mortality in children under 5 years of age in Equatorial Guinea. Early appropriate treatment can reduce progression of the illness to severe stages, thus reducing of mortality, morbidity and onward transmission. The factors that contribute to malaria treatment delay have not been studied previously in Equatorial Guinea. The objective of this study was to assess the determinants of delay in seeking malaria treatment for children in the Bata district, in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
44
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 27 publications
13
44
5
1
Order By: Relevance
“…Some other studies highlighted that knowledge about malaria symptoms may not be enough to explain prompt and adequate care seeking alone [17, 19, 41, 42]. The current finding is consistent with a previous study that reported malaria knowledge could improve malaria health related behaviours independent of other factors [19].…”
Section: Discussionsupporting
confidence: 91%
“…Some other studies highlighted that knowledge about malaria symptoms may not be enough to explain prompt and adequate care seeking alone [17, 19, 41, 42]. The current finding is consistent with a previous study that reported malaria knowledge could improve malaria health related behaviours independent of other factors [19].…”
Section: Discussionsupporting
confidence: 91%
“…The financial dependence of women in sub-Saharan Africa may lead the latter to wait until the husband pays the costs of consultation and travel to go to a health facility. The role of monogamous marriage in the late treatment of malaria in our study, where 78% of the married mothers or babysitters were concerned, was reported by other results in Africa [24].…”
Section: 3 Determinants Of Delays In Hcumt In Childrensupporting
confidence: 75%
“…Although rural caregivers had 3 times lower odds of mentioning fever as a symptom, they had 4 times the odds of mentioning convulsions compared to urban caregivers. In Bata district, delay in seeking treatment for children with malaria is more frequently in rural households [22] and this delay could be responsible for the more frequent reports of convulsions in that area. However, the occurrence of convulsions in Bata district seems not to be linked to a prompt or different pattern in seeking treatment [19], suggesting that there is a need for more study about caregiver awareness of malaria convulsions and disease severity in children.…”
Section: Discussionmentioning
confidence: 99%
“…As described in detail previously [22], the District’s public health facilities comprise a network of ten health centres, two rural and eight urban, and one regional hospital located in the city of Bata. There are also private health facilities in the Bata District, including two hospitals, and about 23 clinics, all in the urban area of Bata city.…”
Section: Methodsmentioning
confidence: 99%